2012
DOI: 10.1007/s00425-012-1741-8
|View full text |Cite
|
Sign up to set email alerts
|

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies

Abstract: Each plant species in nature harbors endophytes, a community of microbes living within host plants without causing any disease symptom. However, the exploitation of endophyte-based phytoprotectants is hampered by the paucity of mechanistic understandings of endophyte-plant interaction. We here reported two endophytic Streptomyces isolates IFB-A02 and IFB-A03 recovered from a stress-tolerant dicotyledonous plant Artemisia annua L. After the determination of their non-pathogenicity at the genomic level and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…For example, dTDP-glucose 4,6-dehydratase involved in streptomycin biosynthesis is more abundant during plant bolting and flowering. Streptomycin is an antibiotic mainly produced by Streptomyces and it is antagonistic against grampositive and -negative bacteria and has been shown to enhance plant defenses and trigger systemic resistance (Schatz et al, 2005;Conn et al, 2008;Lin et al, 2012). Additionally, we observe that dTDPglucose-4,6-dehydratase positively correlates with the root exudate compound myo-Inositol which increases streptomycin biosynthesis (Majumdar and Kutzner, 1962;Heding, 1964).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, dTDP-glucose 4,6-dehydratase involved in streptomycin biosynthesis is more abundant during plant bolting and flowering. Streptomycin is an antibiotic mainly produced by Streptomyces and it is antagonistic against grampositive and -negative bacteria and has been shown to enhance plant defenses and trigger systemic resistance (Schatz et al, 2005;Conn et al, 2008;Lin et al, 2012). Additionally, we observe that dTDPglucose-4,6-dehydratase positively correlates with the root exudate compound myo-Inositol which increases streptomycin biosynthesis (Majumdar and Kutzner, 1962;Heding, 1964).…”
Section: Discussionmentioning
confidence: 68%
“…Actinobacteria, on the other hand, has recently been associated with disease suppressive soils (Mendes et al, 2011). Streptomyces species, which were significantly more abundant in the vegetative stage of Arabidopsis (Supplementary Figure S4E), are able to increase root nodulation efficiency and promote plant growth of the legume Pisum sativum (Tokala et al, 2002) while simultaneously triggering plant defense in Arabidopsis or apple trees (Cohen et al, 2005;Conn et al, 2008;Lin et al, 2012). On the other hand, Bacteroidetes' role in the rhizosphere has not yet been elucidated but it has been reported that they are important contributors to nutrient turnover in the soil (Yousuf et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies on the defense responses induced by S. scabies in potato exist, focusing mostly on responses in individual tubers and not entire plant systems (16), there have been studies performed in A. thaliana plant systems. Interestingly, the inoculation of A. thaliana seedlings with S. scabies, after preinoculation with a nonpathogenic endophytic Streptomyces isolate, also induced an SA-related SAR response (23). Some reports on the effect of thaxtomin A, the phytotoxin responsible for scab symptoms, have also been accomplished in A. thaliana.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, S. scabies' ability to induce SAR in potato plants has never been studied. However, some reports suggest that S. scabies, or the thaxtomin A it produces, are capable of inducing defense responses in A. thaliana (5,14,15,23).…”
mentioning
confidence: 99%
“…There is evidence for symbiosis with arbuscular mycorrhizal fungi, but no report exists on a symbiosis with endophytic Streptomyces ). Up to now only a few species of the large plant family of Asteraceae were reported to interact with endophytic Streptomyces, among them Artemisia annua, which is also a plant with known medicinal properties (Sardi et al 1992;Jiménez-Esquilín and Roane 2005;Castillo et al 2007;Lin et al 2012;Tanvir et al 2014).…”
Section: Introductionmentioning
confidence: 99%